KEKERASAN (SEKSUAL) DALAM DRAMA A STREETCAR NAMED DESIRE KARYA TENNESSEE WILLIAMS TINJAUAN ANALISIS WACANA KRITIS MODEL VAN DIJK - Eka Susylowati (Kantor Bahasa Provinsi Maluku Utara, 2022)
This study aims to describe the portrait of social reality in American society related to sexual violence in the drama A Streetcar Named Desire. In this study, a qualitative method was used to show the data descriptively using the Van Dijk model of critical discourse analysis approach. The data in this study came from the drama A Streetcar Named Desire. The data was collected using the observation method, then continued with the note taking technique. The results of this study indicate that the sociocultural life of American society is full of violence, gambling and sex. Through Van Dijk's analysis, it can be concluded that the discourse construction of A Streetcar Named Desire with violence as a theme is a text constructed from sociocultural phenomena in America. The strong patriarchal culture in America is the social context behind the creation of texts with the theme of violence in the drama A Streetcar Named Desire. In this context, an author with a family life full of violence can be described in the life in the drama. Such family life is a representation of family life in America that is full of the violence.